Thermal treatment of attapulgite for phosphate removal: A cheap and natural adsorbent with high adsorption capacity - Kim, Mun Ju; Lee, Jung Hun; Lee, Chang Gu; Park, Seong Jik (Desalination and Water Treatment, 2018)
Attapulgite was used for the removal of phosphate in aqueous solution and was thermally treated to improve its phosphate adsorption capacity. Attapulgite treated at different temperatures was analyzed to characterize its physical and chemical properties and quantify its phosphate removal efficiency. Attapulgite treated at 700°C (700-ATP) was found to remove phosphate more efficiently than the attapulgite treated at the other temperatures did. The pseudo-second-order and Freundlich models were appropriate for describing phosphate adsorption onto 700-ATP for various reaction times and initial phosphate concentrations, respectively. Both enthalpy and entropy increased during phosphate adsorption onto 700-ATP. An increase in solution pH from 3 to 11 led to a decrease in the adsorption amount of phosphate from 51.53 to 42.43 mg/g. The influence of competitive anions on the phosphate adsorption was as follows: HCO3 – > SO4 2– > NO3 – . Attempts to reutilize the 700-ATP with deionized water were not successful. Phosphorus fractionation experimentation showed that most of the phosphate in 700-ATP was present in residual form. Phosphorus was strongly adsorbed onto 700-ATP. This study demonstrated that thermal treatment is a simple but effective way to improve the phosphorus removal efficiency of attapulgite and 700-ATP is a low-cost, natural, and abundant material for the removal of phosphate from aqueous solution.
Keywords: Adsorption; Attapulgite; Batch experiment; Ca elution; P fractionation; Thermal treatment